Medina to House of Wisdom: Islam and Muslim Contribution to Science of History - Zhilwan Tahir; Abdulwahed Jalal Nori (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This paper explores the pivotal role of Islam and Muslim scholars in advancing the science of history from the early days of Medina to the flourishing intellectual center of The House of Wisdom. This study aims to provide a comprehensive understanding of the evolution of historical methodologies, preservation of historical knowledge, and cultural essence in both pre-Islamic and Islamic realms. Employing a qualitative research approach, the paper analyzes various genres of Islamic historical writing, including Tabaqat, Tarajim, geographical history, and universal history, as well as the methodologies used in documenting and analyzing historical events, such as logical interpretation, natural law interpretation, and speculative interpretation. Through an examination of libraries, scholars, and the transmission of historical knowledge, the paper highlights the enduring legacy of Islamic historiography and its impact on subsequent historiographical traditions. The research findings underscore the significance of Islamic historiography in shaping our understanding of the past and its ongoing relevance in modern academic research, while also suggesting avenues for future research to further explore the rich heritage of Islamic historical scholarship.